G5 Sahel Region Country Climate and Development Report - World Bank Group (Washington, DC: World Bank, 2022)
The five countries of Burkina Faso, Chad, Mali, Mauritania, and Niger (the G5) in the Sahel region of Africa are among the least developed countries in the world. The now regular and growing climate shocks are causing large losses in outputs, reducing human capital accumulation, and leading to potentially devastating ecological and economic tipping points in the region. This World Bank country climate development report (CCDR) has examined the most critical actions and policy changes needed to accelerate the region's economic recovery, sustainable and inclusive development, and adaptation to the impacts of climate change. This report has three main messages. First, the opportunities for a resilient and lower-carbon development of the G5 countries are significant. They can reverse environmental degradation and maximize the benefits of climate action for the poor. Second, rapid, resilient, and inclusive growth is both the best form of adaptation to climate change and the best strategy for meeting development goals in an effective, sustainable, and productive manner. Third, the costs of inaction are far greater than the costs of action. Early and targeted action on policies and programs presented in this report can move the G5 Sahel countries towards a greener, more resilient, prosperous, and inclusive future.